PENGARUH PROFITABILITAS DAN SOLVABILITAS TERHADAP HARGA SAHAM PERUSAHAAN SEKTOR PROPERTI YANG TERDAFTAR DI BEI PADA TAHUN 2012-2016 - Agung Hernando Harsono; Dwi Budiadi; Andrea Gideon (CAHAYA AKTIVA, 2019)
This study aims to find out about the influence of profitability and solvency of the company on stock prices. The financial ratios studied are Return on Assets and Debt to Equity Ratio as independent variables and stock prices as the dependent variable. The number of samples used in this study are property sector companies listed on the IDX from 2012 - 2016. The statistical method used in this study is multiple regression method. The results of this study indicate that the ratio of Return on Assets, and Debt to Equity Ratio is simultaneously statistically significant effect on stock prices. While statistically partial the ratio of Debt to Equity Ratio does not have a significant effect on stock prices that will be traded on the stock exchange. Keywords: Profitability (ROA), Solvency (DER), Share Prices.